Quantitative Analysis of the Evolution of Production–Living–Ecological Space in Traditional Villages: A Comparative Study of Rural Areas in Tibet - Yue Tang; Li Zhu; Xiaokang Wang (Land)
Since the introduction of the rural revitalization strategy by the 19th National Congress of the Communist Party of China in 2017, there have been significant transformations in the production–living–ecological space (PLES) within villages. Evaluating and enhancing villages’ PLES are crucial for fostering sustainable development. Therefore, this study utilized a multi-scale environmental assessment model and mathematical approach to conduct horizontal and vertical nested correlation analyses of indicators at different levels through a path analysis, a Spearman correlation analysis, a variance analysis, the entropy weight method, data simulation, and other methods to establish a “three-dimensional” comprehensive evaluation system for traditional village PLES. The findings indicate the following: (1) The ecological space of traditional villages in Tibet significantly impacts the overall environment of the PLES, with the components’ impact ranked as follows: ecological space > production space > living space. Furthermore, industry and tourism resources show a significant positive correlation with traditional villages’ PLES; (2) There are no significant differences in natural environmental factors, such as air relative humidity, temperature, humidity index, and wind efficiency index among traditional villages in neighboring cities in Tibet. However, they all possess profound ecological and cultural heritage; (3) There are notable disparities in living space between traditional villages in Lhasa and Nyingchi, indicating unbalanced development. It is evident that traditional village construction should not only focus on the development of certain PLES but also pay attention to the balanced development of the overall spatial environment. This study holds great significance for enhancing the living environment of traditional villages in Tibet and promoting sustainable development through protection efforts in these villages.